Efecto genético de toros usados vía inseminación artificial sobre la producción láctea de la estación experimental El Mantaro, Junín, Perú - Meza R., Elmer (2021)
The present study aimed to determine the contribution of the genetic effect of bulls used via artificial insemination on the dairy production of Brown Swiss cows from the El Mantaro Agricultural Experiment Station of the National University of Central Peru, in terms of daily milk production (PLD) and by lactation (PLC). In total, 112 lactations were used, from a total of 49 cows, daughters of 7 Brown Swiss bulls, standardized to 305 days (PLE) and two milking by non-linear projection. The statistical analysis was carried out by using a mixed linear model, considering as fixed factors the number of lactations, year, season and age at calving of the cow, and as a random factor the genetic effect of the bull. Corrected phenotypic means were obtained for PLD and PLC with the correction factors obtained from the model, and predictions of the predicted transmission ability (PTA) of the evaluated bulls and their respective precisions. The corrected phenotypic means ranged from 9.39 ± 0.62 kg to 12.18 ± 0.87 kg for PLD and from 3 218.8 ± 40.2 kg to 4 690.4 ± 54.6 kg for PLC, while the PTA of the bulls ranged from -2.82 to 1.98 kg/day for PLD and from -841.55 to 630.33 kg/lactation for PLC, registering precision levels of 58.87 to 78.34%. The results show an important differential in the genetic level of the bulls and the potential use of some to contribute to the increase in milk production in the study area.